Comparison of Extent and Severity of Coronary Artery Disease in Patients with and without Diabetes Mellitus Presenting with Non ST-Segment Elevation Myocardial Infarction - Timalsena, Birat Krishna; Malla, Rabi; Maskey, Arun; Rajbhandari, Sujeeb; Parajuli, Aryan; Basnet, Sonu; Acharya, Dikshanta; Lamichhane, Saugat; Poudel, Samir Kumar; Karki, Parag (Nepalese Heart Journal, 2020)
Background and Aims: Diabetic patients are at increased risk of developing coronary artery disease. This study was conducted with the aim to compare the extent and severity of coronary artery disease in patients with and without diabetes presenting with non ST segment elevation myocardial infarction (NSTEMI). Methods: This was a single center, hospital based, cross sectional, observational comparative study in which total 172 patients presenting with NSTEMI were divided into two groups of 86 patients each based on presence or absence of diabetes mellitus. Demographic, laboratory and angiographic data were analysed and compared between two groups. Results: Among 86 patients enrolled in each group demographic characteristics and risk profile were not significantly different except for smoking status. Significant number of non-diabetics were current smoker (26.7% vs. 9.3%; p < 0.01). Hypertension was the most common risk factor in both groups. Non-diabetic patients had significantly high single vessel disease when compared to diabetics (11.6% vs 24.4%; p=0.03) while multivessel disease was significantly higher among diabetics (80.2% vs 59.3%; p<0.01). Diabetics had severe coronary artery disease with significantly high Gensini score (71.18±39.03 vs 59.84±33.68; p=0.04). There was no difference in terms of type of vessel affected. Conclusions: Diabetic patients presenting with NSTEMI are likely to have more severe and extensive coronary artery disease compared to non-diabetic patients.